Age of revolutions eaudiobook Progress and backlash from 1600 to the present. - Zakaria, Fareed (Simon & Schuster Audio, 2024)
The internationally bestselling author explores the revolutions—past and present—that define the chaotic, polarized, and unstable age in which we live. Populist rage, ideological fracture, economic and technological shocks, geopolitical dangers, and an international system studded with catastrophic risk—the early decades of the 21st century may be one of the most revolutionary periods in modern history. But they are not the first. Humans have lived, and thrived, through more than one great realignment. What makes an age a revolutionary one? And how do they end? In this major new work, Fareed Zakaria masterfully investigates eras that have shattered and shaped humanity. Four such periods hold profound lessons for today. First, in 17th-century Netherlands a series of transformations made that tiny land the richest in the world—and created modern politics as we know it today. The "Glorious Revolution" in Britain showed that major political change could happen peacefully. Next, the French Revolution, a dramatic decade and a half that devoured its ideological children and left a bloody legacy that haunts us to this day. Finally, the mother of all revolutions, the Industrial Revolution, which catapulted Britain and the US to global dominance and created the modern world. Against these paradigm-shifting historical eras, Zakaria describes our current situation, unpacking the four revolutions we are living through now; in globalization, technology, identity, and geopolitics. As few public intellectuals can, Zakaria combines intellectual range, deep historical insight, and uncanny prescience to reframe and illuminate a turbulent present.